Occurrence of community-acquired Panton-Valentine leukocidin-producing and enterotoxin-producing methicillin-resistant staphylococci in companion dogs - Morenike O. ADEOLA; Faith I. AKINNIBOSUN; Odaro S. IMADE (Studia Universitatis Babeș-Bolyai. Biologia)
In Nigeria, available data on drug-resistant bacterial infections that are caused by companion dogs are scarce. Hence the present study evaluated the occurrence of some community-acquired toxigenic methicillin-resistant staphylococci (MRS) on companion dogs harboured in Nigerian homes, as a pointer to the extent of exposure of humans to these pathogens. Samples were collected from 70 healthy companion dogs during dry and rainy season periods by swabbing a 125 cm2 fur area on the lumbar and thoracic sites.  Phenotypic tests, Kirby Bauer disc diffusion test and 16S rRNA gene analysis were used to identify presumptive colonies of staphylococci and MRS. Molecular methods were employed to detect Panton-Valentine leukocidin (PVL) and prototypic enterotoxin B in MRS isolates. The counts of staphylococci on fur of companion dogs during the rainy season exceeded usual limits of bacteria (≤ 2.54 log10 CFU cm-2) on a healthy dog, thus, suggesting that companion dogs harboured in homes situated in Nigeria may be reservoirs of bacteria, especially during rainy season. The mean counts of staphylococci during the rainy season were estimated at 3.09 ± 2.78 log10 CFU cm-2 and 2.77 ± 2.43 log10 CFU cm-2 in Edo and Delta States, respectively. The main Staphylococcus species that were carried on fur of companion dogs included S. pseudintermedius, S. aureus, S. epidermidis, S. simulans and S. saprophyticus. Amongst the staphylococci, expression of methicillin and multidrug resistance was mainly exhibited by S. pseudintermedius and S. aureus, while enterotoxigenicity was mainly expressed by methicillin-resistant S. aureus. Enterotoxigenic S. aureus was carried on the fur of companion dogs during the rainy season at estimated prevalence of 8.57% in both Edo and Delta States, respectively; while PVL-producing S. aureus was estimated at 5.71% and 2.86%, with PVL-producing S. pseudintermedius estimated at 25.71% and 34.29%, respectively. The high prevalence of toxigenic-producing isolates seen on the fur of companion dogs, especially during rainy season, could pose a risk for humans, particularly those that harbour pet dogs at their homes.